Lithiation-induced crystal restructuring of hydrothermally prepared Sn/TiO2 nanocrystallite with substantially enhanced capacity and cycling performance for lithium-ion battery. Issue 54 (18th May 2016) - Chen, Tsan-Yao; Liu, Yu-Ting; Wu, Ping-Ching; Hu, Chih-Wei; Yang, Po-Wei; Hsu, Liang-Ching; Lee, Chih-Hao; Chang, Chia-Chin
Abstract : Sn dopants undergo restructuring into Ti sites of TiO2 upon lithiation reaction. These Sn dopants attract Li to form local SnLi x alloys, which sufficiently increase the capacity of Sn-substituted TiO2 as a negative electrode material. Abstract : A Sn-doped TiO2 nanocrystallite with the composition of Sn0.1 Ti0.9 O2 was prepared by hydrothermal co-precipitation followed by thermal annealing at 600 °C for 2 hours. Results combining high-resolution transmission electron microscopy, in situ XRD, ex situ XAS, and electrochemical impedance spectroscopy indicate that Sn0.1 Ti0.9 O2 underwent restructuring to give Sn-substituted TiO2 (Sn to Ti sites) by a lithiation reaction at 0.1C in a lithium-ion battery. The capacity and cyclability of Sn0.1 Ti0.9 O2 were increased by ∼73% (to ∼598 mA h g −1 ) and ∼17.4% compared with those of TiO2 (∼345 mA h g −1 and ∼22%) at 0.1C until the 250 th cycle. Our results proved that these improvements were caused by the self-aligned formation of Sn–Ti oxide and the subsequent formation of a SnLi x local alloy at Ti sites.